Efektivitas Aplikasi Strokecare Terhadap Peningkatan Kepatuhan Kontrol Pasien Stroke di Poliklinik Saraf RSPAD Gatot Soebroto: Quasi Experimental Pretest–Posttest Control Group Study - Tomi Suranta; Argi Virgona Bangun; Rita Fitri Yulita; Cecep Eli Kosasih; Ismafiaty Ismafiaty (Universitas Pahlawan Tuanku Tambusai, 2026)
Stroke is a leading cause of mortality and long-term disability worldwide. Routine follow-up is essential to prevent recurrent stroke and optimize recovery; however, adherence remains low because of limited health education, inadequate reminder systems, and insufficient use of digital health technologies. The StrokeCare mobile application was developed to provide continuous digital education and improve follow-up adherence among stroke patients. Objective this study aimed to evaluate the effectiveness of the StrokeCare mobile application in improving follow-up adherence among stroke patients at the Neurology Outpatient Clinic of RSPAD Gatot Soebroto. Methods a quasi-experimental study with a pretest–posttest control group design was conducted among 56 stroke patients, comprising 28 participants in the intervention group and 28 in the control group. The intervention group received education using the StrokeCare application for four weeks, while the control group received conventional health education. Follow-up adherence was assessed before and after the intervention. Data were analyzed using the Shapiro–Wilk test, Wilcoxon Signed-Rank Test, and Mann–Whitney U Test with a significance level of p < 0.05. Results pretest analysis showed no significant difference between groups (p = 0.557). After the intervention, follow-up adherence was significantly higher in the intervention group than in the control group (p < 0.001). The intervention group demonstrated a greater improvement in adherence scores (56.64–93.71) than the control group (55.89–65.07). Conclusion the StrokeCare mobile application effectively improved follow-up adherence among stroke patients and may serve as an innovative digital health education tool to support continuity of outpatient stroke care.